1
$\begingroup$

I'm trying to evaluate the sum given below

$$ S(x,y) = \frac{1}{k!}\sum_{j=0}^k \binom{k}{j} (-x)^j y^{k-j} j! $$

where $x,y > 0$. Is there any clever closed form way of writing this sum? If not, maybe there is a clever way of writing it as a product? I was considering products of $(y-jx)$ factors perhaps $\pm (y-x)^k$ but could not get this work. Any ideas?

$\endgroup$
2
$\begingroup$

Since ${k \choose j} = {k \choose k-j} = \frac{k!}{j!(k-j)!}$, upon making the substitution $j \leftrightarrow k-j$ you can write your sum as

$$ S(x,y) = (-x)^k \sum_{j=0}^k \frac{1}{j!} \left( - \frac{y}{x} \right)^j = (-x)^k S(1, -y/x) \; .$$

Now we recognize $S(u) := S(1, u) = \sum_{j=0}^k \frac{u^j}{j!}$ as the $k$-th partial sum of the MacLaurin expansion of $e^{u}$, which admits a closed form in terms of the (incomplete) Gamma function, as expressed in this MSE post. This gives some perspective on the other possible 'closed forms' one might expects.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.